2020
DOI: 10.3390/ma13225117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Equal Channel Angular Pressing on Mechanical Behavior and Corrosion Resistance of Hot-Rolled Ti-2Fe-0.1B Alloy

Abstract: In the present study, the unique bimodal grain size distribution microstructure with the ultrafine substrate and embedded macro grains was fabricated by a traditional hot-rolling process in a novel low-cost Ti-2Fe-0.1B titanium alloy, which possesses a good combination of strength (around 663 MPa) and ductility (around 30%) without any post heat treatment. Meanwhile, the mechanical behavior and corrosion resistance of hot-rolled Ti-2Fe-0.1B alloy after equal channel angular pressing (ECAP) deformation were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Titanium alloy is an important strategic metal material with low density, high specific strength, and excellent corrosion resistance [ 1 , 2 , 3 ]. Such alloys, sometimes referred to as “air metal”, “marine metal”, or “smart metal”, are used in many applications in the aerospace, marine, chemical, and medical fields [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloy is an important strategic metal material with low density, high specific strength, and excellent corrosion resistance [ 1 , 2 , 3 ]. Such alloys, sometimes referred to as “air metal”, “marine metal”, or “smart metal”, are used in many applications in the aerospace, marine, chemical, and medical fields [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Fe and B element additions can benefit the refinement of ingot structure; meanwhile, the reduction in grain size of Ti-2Fe-0.1B alloy by ECAP can effectively improve the segregation of elements and weaken the galvanic effect [34,35]. Our group [22] characterized the surface morphology of CG and UFG Ti-2Fe-0.1B after potentiodynamic scanning by SEM, and it was found that the corrosion pit volume produced by selective dissolution due to the galvanic effect in CG Ti-2Fe-0.1B was significantly higher than that in UFG Ti-2Fe-0.1B. This result proves that in UFG Ti-2Fe-0.1B, the distribution of alloying elements in the α and β phases is more uniform and the microstructure is more homogeneous, which could reduce the risk of pitting corrosion when the fresh substrate is exposed to corrosive medium because the passivation film ruptures under the influence of external tensile stress.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the microstructure of UFG Ti-2Fe-0.1B alloy is mainly composed of dislocation cells and several subgrains; the microstructure is totally blurry due to a large number of dislocation tangles and dislocation piles; all the grains have high internal stress after suffering severe deformation; and the undistorted grains with clear grain boundaries and regular shapes are rarely seen. The microstructure of UFG Ti-2Fe-0.1B is more uniform, and the average grain size is 0.24 µm [22].…”
Section: Tem Microstructural Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, B microalloying is famous for its use in titanium alloys to improve the ingot structure, which is of benefit for the consequential forging and rolling process [21]. Hence, a novel Ti-2Fe-0.1B titanium alloy was designed by our team, developed and additively manufactured using several advanced technologies, such as severe plastic deformation and a thermal hydrogenated process [22][23][24]. As we all know, the B element addition in titanium alloys could benefit their thermal stability because of the TiB needles present at the grain boundaries, which restrict their mobility at high temperatures due to the Zener drag mechanism.…”
Section: Introductionmentioning
confidence: 99%